VD_FINDINFO HC / 2010 / 157 vom 22. Januar 2010 - VD Tribunal cantonal (2010)
CONTRAT DE TRAVAIL, PRESTATION INSUFFISANTE, RÉSILIATION | 8 CC, 335 al. 1 CO, 336 al. 1 let. d CO, 451 ch. 2 CPC, 452 al. 2 CPC, 46 LJT